CONTROLLABILITY OF NON-CONTACT MAGNETIC PULSE STRAIGHTENING - A.V. Gnatov (National Technical University "Kharkiv Polytechnic Institute", 2013)
Experimental research on dosing and controllability of non-contact magnetic pulse straightening is presented in the article. Illustrations of dosed magnetic-pulse action are given by the example of an element of a Subaru body panel. It is demonstrated that non-contact straightening does not damage the protective paint coating of a car body